Teacher Training and Inclusive Education: Analysis of the Contents of Pedagogy Courses in Unesp and USP - Poker, Rosimar Bortolini [UNESP]; Costa Milanez, Simone Ghedini [UNESP] (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2015)
In Brazil, the current educational model, based on national legislation and international movements, defends the proposal of inclusive education where all students, respecting their specificities, learn together. It becomes essential to the occurrence of changes in teacher training. In this context, the research sought to understand and analyze the content present in the teaching plan of the Pedagogy Courses in the Universidade Estadual Paulista (Unesp) and the Universidade de Sao Paulo (USP), directly related to inclusive education by checking whether they are meeting the new requirements triggered by inclusion. Therefore, the teaching plan of compulsory subjects of these two courses were collected and then the contents that dealt directly with issues related to inclusive education were identified, analyzed and compared. The results showed that there are recurring content regarding inclusive education that are present in most courses and there are also many different contents that are present in only one or two courses. It appears from hence the need to discuss, think and elect the fundamental contents that pedagogy courses must meet, providing all teachers with capable training to act from the perspective of inclusive education.
Keywords: Teacher Training; Curriculum Content; Educational Inclusion; Pedagogy Course